Indonesia’s Diplomatic Actions in the Israel-Palestine Conflict - Ayun, Shofaa Qurrota; Istifarin, Afianti; Hidayatullah, Achmad Dini; Soleh, Badrus (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2024)
Indonesia has consistently fought for Palestinian independence, utilizing parliamentary diplomacy to enhance its role in international efforts that support the establishment of an independent Palestinian state. The problem formulations in this study are (1) what factors inhibit the Israeli-Palestinian conflict? (2) what is the role of Indonesian diplomacy in the Israeli-Palestinian conflict? This study aims to examine Indonesia's diplomatic actions towards the conflict between Israel and Palestine. This study uses a descriptive-qualitative method. The data sources in this study are books, journals, and electronic news from several related objects. The results of this study are in the case of the Indonesian Hospital in Palestine, the International Criminal Court (ICC) is the proper party to adjudicate Israel's war violations of International Humanitarian Law and Human Rights. The UN Security Council should not obstruct the enforcement of violations of international law in political relations. The veto cannot be exercised if it conflicts with jus cogens norms or undermines the ability of other Security Council members to collaborate in response to grave violations of human rights. Indonesia's Foreign Minister condemned the situation in Gaza as a human rights violation and recommended an immediate ceasefire, rejection of double standards, and support for accountable mechanisms. Indonesia also highlighted the Palestinian people's right to self-determination at the International Court of Justice. As a UN Human Rights Council member, Indonesia made justice for the Palestinian people a key issue, recommending three important actions: strengthening the human rights ecosystem, addressing the global humanitarian crisis, and promoting human rights equally.